Comparative Analysis of Leguminous Substitutes Versus Conventional Concentrates on Nutrient Digestibility and Rumen Fermentation in Livestock - Ezi Masdia Putri; Windu Negara; Ruslan Abdul Gopar; Hikmah Agustina Parastiwi; Riris Delima Purba; Putut Suryo Negoro; Faheem Ahmed Khan; Bayu Andri Atmoko; Mardiati Zain; Riki Hiskia Candra; Ummi Amanah (Andalasian Livestock, 2025)
Concentrate can improve livestock productivity due to its high protein content. Meanwhile, a high proportion of concentrate consumption in livestock can decrease the pH of the rumen and lead to a decrease in rumen performance. Leguminous plants that have high protein and are abundantly available are a potential source of protein and concentrate substitutes in livestock diets. This study aimed to evaluate the effect of Leucaena leucocephala (LL) and Indigofera zollingeriana (IZ) as concentrate substitutes in RDP: RUP-concentrate-based diet on degradation of dry matter degradability (DMD) and organic matter (OMD), digestible neutral detergent fiber (dNDF), in vitro true digestibility (IVTD), pH value, NH3 concentration, and total gas production. This study used a Randomized Block Design, consisting of seven treatments with four replications. The treatments were: T1 = control consist of 40% Pennisetum clandestinum (PC) and 60% concentrate (C) (RDP: RUP of concentrate = 60%:40% of crude protein), T2 = 40% PC + 45% C + 15% LL, T3 = 40% PC + 45% C + 15% IZ, T4 = 40% PC + 30% C + 30% LL, T5 = 40% PC + 30% C + 30% IZ, T6 = 40% PC + 30% C + 15% LL + 15% IZ, T7 = 40% PC + 30% LL + 30% IZ. This study reported that leguminous as concentrate substitutes in RDP: RUP-concentrate-based diet significantly affected nutrient digestibility and total gas production, while pH value and NH3 concentration did not differ among experimental diets. The supplementation of LL 15-30% and IZ 15-30% in RDP: RUP-based diet increases DMD, OMD, IVTD, and total gas production. The combination of LL and IZ 15-30% in RDP: RUP-based diets tend to depress OMD, while other parameters did not differ among experimental diets. The highest DMD, OMD, IVTD, and total gas production were observed in the experimental diet with 30% of IZ substitutes in the RDP: RUP-concentrate-based diet. In conclusion, 30% Indigofera zollingeriana as a concentrate substitute in RDP: RUP-concentrate-based diet can increase nutrient digestibility and optimize rumen fermentation characteristics.